2019
DOI: 10.1002/pat.4782
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardant and toughening behaviors of bio‐based DOPO‐containing curing agent in epoxy thermoset

Abstract: Based on bio-based furfural, a phosphorus-containing curing agent (FPD) was successfully synthesized, via the addition reaction between 9,10-dihydro-9-oxa-10 phosphaphenanthrene-10-oxide (DOPO) and furfural-derived Schiff base. Then, as co-curing agent, FPD was used to prepare flame retardant epoxy thermosets (EP) cured by 4, 4′-diaminodiphenyl methane. The incorporated FPD improved the flame retardancy and toughness of epoxy thermoset, simultaneously. When 5 wt% FPD was added into EP, the FPD/EP achieved 35.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
(47 reference statements)
1
28
0
1
Order By: Relevance
“…This is because the flame retardancy of epoxy thermoset can be improved efficiently by introducing phosphorus‐containing flame retardants or flame‐retardant groups 14,15 . These reported phosphorus‐containing flame retardants mainly included phosphaphenanthrene‐containing compound, phosphazene‐containing compound, phosphate ester, phosphate, and hypophosphite, among which the phosphaphenanthrene‐containing compounds has been the focus of attention, due to their low addition and high flame‐retardant efficiency 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…This is because the flame retardancy of epoxy thermoset can be improved efficiently by introducing phosphorus‐containing flame retardants or flame‐retardant groups 14,15 . These reported phosphorus‐containing flame retardants mainly included phosphaphenanthrene‐containing compound, phosphazene‐containing compound, phosphate ester, phosphate, and hypophosphite, among which the phosphaphenanthrene‐containing compounds has been the focus of attention, due to their low addition and high flame‐retardant efficiency 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…However, the fire-retardant of EP cannot be effectively improved when DOPO was used alone. 17 To further enhance the flame-retardant efficiency of DOPO and its derivatives, researchers have devoted extensive effort, and noted that a feasible method is to introduce nitrogen-containing components into its structure, where phosphophenanthrene group and N-containing structures would exert a P N synergistic flame-retardant effect. [18][19][20] For instance, Cheng et al 3 synthesized a P/Ncontaining flame retardant (PPT) using DOPO, phenylphosphonic dichloride, p-hydroxybenzaldehyde and 3-amino-1H-1,2,4-triazole as raw material.…”
Section: Introductionmentioning
confidence: 99%
“…DOPO can play dual flame‐retardant effect in the gas and condensed phases through free radical quenching and charring effect. However, the fire‐retardant of EP cannot be effectively improved when DOPO was used alone 17 . To further enhance the flame‐retardant efficiency of DOPO and its derivatives, researchers have devoted extensive effort, and noted that a feasible method is to introduce nitrogen‐containing components into its structure, where phosphophenanthrene group and N‐containing structures would exert a PN synergistic flame‐retardant effect 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the incorporation of flexible chain structures, the free movement of the chain segments was increased under the action of an external force, and the free segments were arranged in an orderly manner in the direction of tension until fractured. Thereby, the cured epoxy resin experienced an intricate fracture path, which would consume much more impact energy, and ultimately demonstrated tough fracture characteristics 33 . When 5% HCOGE was incorporated, the fractured surface of the cured product had abundant irregular broken cracks and scaly fragments, and we observed that there were many cavities.…”
Section: Resultsmentioning
confidence: 76%